PENGARUH PENGGUNAAN MULSA PADA PERTUMBUHAN DAN PRODUKSI TANAMAN KENTANG (Solanum tuberosum L.) DI DATARAN MENENGAH - Giavirna J. Enoch; Edy F. Lengkong; Jantje Pongoh (COCOS, 2017)
ABSTRACTThe objective of this study was to study the effect of mulch use on the growth and production of potato crops in the middle plains and to determine the type of mulch suitable for potato crops in the middle plains. This research was conducted in Tompaso II Village District Tompaso, Regency of Minahasa, with the height of 765 mdpl. This study was implemented for 4 months, from May to August 2016. This study used a Completely Randomized Design experiment consisting of 3 treatments with different repetitions. The Treatments are Plastic Silver Black Mulch repeated 3 times, Straw Mulch repeated as much as 4 times and Control repeated 6 times. Based on the result of statistical analysis, there is no significant difference between the treatment can be caused by environmental factors and genetic factors seedings are planted. Environmental factors such as temperature, humidity, rainfall, light intensity, soil fertility, and the presence or absence of pests and diseases will determine growth and production in plants.Keywords: the potatos, medium plains, mulch